EFEKTIVITAS VIDEO KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP IBU TENTANG STUNTING DI WILAYAH KERJA PUSKESMAS BANGEKO KANAN - Armiyanti, Armiyanti; Hanim, Busyra (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
Stunting is a major threat to human quality, as well as a threat to the nation's competitive ability (Ministry of Health, 2018). Because stunting will result in children's intelligence levels not being optimal, making children more vulnerable to disease and in the future could be at risk of decreasing productivity levels. Efforts to prevent stunting should start from the beginning of pregnancy to reduce the risk of stunting in children. The aim of this research is to determine the effectiveness of health videos on mothers' knowledge and attitudes about stunting in the Bangko Kanan Community Health Center Work Area. This research method uses a quasi experimental design. The population used in this research was pregnant women with a sample size of 82 people. The researchers' results were based on the Wilcoxon test with asymp values. The knowledge sig is 0.00 and the attitude is 0.01 (<0.05), meaning that the health video has an impact on increasing mothers' knowledge and attitudes about stunting in the Bangko Kanan Community Health Center working area. It is hoped that the research can become a reference for health workers in providing health promotion to increase knowledge and attitudes of pregnant women about stunting